The association between vitamin D deficiency and risk of renal event: Results from the Korean cohort study for outcomes in patients with chronic kidney disease (KNOW-CKD) - Lee, Juyeon; Bae, Eun Hui; Kim, Soo Wan; Chung, Wookyung; Kim, Yeong Hoon; Oh, Yun Kyu; Kim, Yong-Soo; Oh, Kook-Hwan; Park, Sue K. (Frontiers in Medicine, 2023)
Backgrounds Some observational studies have suggested a possible association between vitamin D deficiency and CKD. However, in most studies, the causality between low levels of vitamin D and risk of renal events could not be explained. We investigated the relationship between vitamin D deficiency and risk of severe CKD stage and renal event in a large-scale prospective cohort study. Methods We used data from a prospective cohort of 2,144 patients with available information on serum 25-hydroxyvitamin D (25(OH)D) levels at baseline from KNOW-CKD, 2011-2015 were included. Vitamin D deficiency was defined as serum 25(OH)D levels < 15 ng/mL. We performed a cross-sectional analysis to elucidate the relationship between 25(OH)D and CKD stage using baseline CKD patient data. We further examined a cohort analysis to clarify the association between 25(OH)D and risk of renal event. Renal event was a composite of the first occurrence of a 50% decline in eGFR from the baseline value or the onset of CKD stage 5 (initiation of dialysis or kidney transplantation) across the follow-up period. We also investigated the associations of vitamin D deficiency with risk of renal event according to diabetes and overweight status. Results Vitamin D deficiency were significantly associated with an increased risk of severe CKD stage – 1.30-fold (95% CI: 1.10-1.69) for 25(OH)D. Deficiency of 25(OH)D with 1.64-fold (95% CI: 1.32-2.65) was related to renal event compared with the reference. Furthermore, vitamin D deficiency patients with presence of DM and overweight status also displayed higher risk than non-deficient patients for risk of renal event. Conclusion Vitamin D deficiency is associated with significantly increased risk of severe CKD stage and renal event.